Assessment of portable chainsaw chains. Issue 4 (1st October 2020) - Robb, William; Nevrkla, Pavel
ABSTRACT: The paper deals with the methodology of qualitative assessment of functional and constructional parameters of portable chainsaw chains. The individual types of chains are compared according to their construction and specifics. This paper identifies and compares typical material properties, as these determine the properties of the chains. Mechanical properties are assessed in accordance with material hardness and metallography. Chemical analysis compares the measurable content of chemical elements in the material. The operational test methodology is designed with the aim to test the specific samples under constant conditions. The study monitors and compares theoretical lifetime and associated economic aspects with the aim to help in the decision-making process in choosing a given chainsaw chain. The methodological procedure of the research study was created and tested. The study addressed chain samples of different manufacturers with reference to chains with round and chisel profiles of cutting links, cutter pitch of 0.325" or 3/8". As the research focused on the checking chain test methodological procedure, not on the results; the tested chains are quoted as samples 1 to 5 to prevent the identification of the manufacturer.